Management Considerations for Unicompartmental Osteoarthritis in Athletic Populations: A Review of the Literature - Wake, Jeffrey L.; Chung, Brandon; Bottoni, Craig R.; Zhou, Liang (The Journal of Knee Surgery, 2022)
Unicompartmental osteoarthritis in the young athlete poses a challenge for both patients and providers. Coronal plane malalignment is frequently a concomitant finding that adds to the complexity of management. Military surgeons are presented unique challenges, in that they must consider optimal joint-preservation methods while returning patients to a high-demand occupational function. Management options range from lifestyle changes to surgical interventions. We present a concise review of the available literature on this subject, with a specific focus on indications and outcomes within the military and young athletic population.
Keywords: orthopaedic surgery; knee osteoarthritis; osteotomies; military; cartilage